2015
DOI: 10.5751/es-06644-200102
|View full text |Cite
|
Sign up to set email alerts
|

Communication and sustainability science teams as complex systems

Abstract: ABSTRACT. Communication is essential to resilience, as interactions among humans influence how social-ecological systems (SES) respond to change. Our research focuses on how specific communication interactions on sustainability science teams, such as how people meet with each other; the ways in which they categorize themselves and others; the decision-making models they use; and their communication competencies affect outcomes. We describe research from a two-year study of communication in Maine's Sustainabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Other recent studies have also investigated and identified processes that lead to success in sustainability science collaborations (Fraser and Schalley, 2009), but have taken a systems approach. Research in this tradition has found that success is related to the patterns of communication behavior and the quality of the relationships formed as a product of the teams (Fraser and Schalley, 2009;Thompson, 2009;McGreavy et al, 2015). In a formative, ethnographic study of a large interdisciplinary team, Thompson (2009) reports that interactions described as "collective communication competencies" (CCC) on the team level influence the collaborative endeavor and its movement toward objectives.…”
Section: Systems View Of Collaborative Teamsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other recent studies have also investigated and identified processes that lead to success in sustainability science collaborations (Fraser and Schalley, 2009), but have taken a systems approach. Research in this tradition has found that success is related to the patterns of communication behavior and the quality of the relationships formed as a product of the teams (Fraser and Schalley, 2009;Thompson, 2009;McGreavy et al, 2015). In a formative, ethnographic study of a large interdisciplinary team, Thompson (2009) reports that interactions described as "collective communication competencies" (CCC) on the team level influence the collaborative endeavor and its movement toward objectives.…”
Section: Systems View Of Collaborative Teamsmentioning
confidence: 99%
“…Conversely, acts of blatant boredom, intentional challenging of expertise, and sarcasm can compromise CCC (Thompson, 2009). McGreavy et al (2015) take this research a step further to identify important communication dimensions of sustainability science teams, when viewed as complex systems. These researchers explore how communication within sustainability science teams influences the results related to team learning and progress toward group goals.…”
Section: Systems View Of Collaborative Teamsmentioning
confidence: 99%
See 2 more Smart Citations
“…This exchange results in social learning [25]. That is, individuals, whether they are scientists or stakeholders, do not innovate in isolation but as a result of interaction and communication with one another [26,27]. In the context of adapting to climate uncertainty both scientists and local water managers have high stakes in participatory research outcomes.…”
Section: Collaborative Modeling As a Participatory Approachmentioning
confidence: 99%